Potret Negara Totaliter dalam Novel Bungkam Suara karya J. S. Khairen - Bintang, Riri Masyitah; Adek, Muhammad (Universitas Negeri Padang, 2024)
This research is conducted to describe the portrait of totalitarian state in Bungkam Suara by J.S. Khairen which is released in January 2023. The story of the novel is about a fiction state called Negara Kesatuan Adat Lawaknesia (NKAL) which is not detected by world map and assumed that no other world but theirs. This research is focus to the portrait of totalitarian state and how NKAL’s citizen respond the government in Bungkam Suara by J.S. Khairen. This research is a qualitative using a descriptive methods. The data were conducted by reading the novel intensively, marking the dialogues and narratives, and inventory the data in the data collection form using smartphone, desktop, and data collection form. The results of this research is revealing that, first, there are 3 of 4 characteristics of totalitarian state (by Hannah Arendt) that found in NKAL; (a) dictatorship; (b) propaganda; (c) terror. There are one characteristic that not found in NKAL is indoctrination. Second, NKAL’s citizen respond the government is civil disobedience that fulfilled all the condition; (a) prudence; (b) communication; (c) publicity; and (d) nonviolence.